Search for new phenomena in events with a photon and missing transverse momentum in pp collisions at √s = 13 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2016)
Results of a search for new phenomena in events with an energetic photon and large missing transverse momentum with the ATLAS experiment at the Large Hadron Collider are reported. The data were collected in proton-proton collisions at a centreof- mass energy of 13 TeV and correspond to an integrated luminosity of 3.2 fb-1. The observed data are in agreement with the Standard Model expectations. Exclusion limits are presented in models of new phenomena including pair production of dark matter candidates or large extra spatial dimensions. In a simpli fied model of dark matter and an axial-vector mediator, the search excludes mediator masses below 710 GeV for dark matter candidate masses below 150 GeV. In an effective theory of dark matter production, values of the suppression scale M* up to 570 GeV are excluded and the effect of truncation for various coupling values is reported. For the ADD large extra spatial dimension model the search places more stringent limits than earlier searches in the same event topology, excluding MD up to about 2.3 (2.8)TeV for two (six) additional spatial dimensions; the limits are reduced by 20-40% depending on the number of additional spatial dimensions when applying a truncation procedure.